Upgrading of biomass by carbonization in hot compressed water - Wiwut Tanthapanichakoon (Songklanakarin Journal of Science and Technology (SJST), 2006)
Carbonization of biomass (corn cob) in hot compressed water was performed using a small bomb reactor at temperature 300-350ºC and pressure 10-18 MPa for 30 min. Then, the solid product or biochar was subjected to various analyses in order to investigate the effects of the carbonization in hot compressed water on the characteristics of the biochar. It was found that the yield of biochar carbonized in hot compressed water at 350ºC and pressure of 10 MPa for 30 min was 44.7%, whereas the yield of biochar carbonized in nitrogen atmosphere at 350ºC is 36.4%. Based on the information obtained from the elemental analyses of the biochar, it was found that the oxygen functional groups in the corn cob were selectively decomposed during the carbonization in hot compressed water. The pyrolysis and combustion behaviors of the biochar were found to be affected significantly by the carbonization in hot compressed water.